The profitability of green banking activities of selected banks (SCBs and PCBs) in Bangladesh: An empirical analysis - Sarker, Sanjoy Kumar; Sharoar, Md Golam; Hossain, Kamal; Bairagi, Mithun; Khan, Feroz (Journal of Asian Business Strategy, 2024)
Global warming is a significant global issue, and Bangladesh is one of the countries most adversely impacted, facing numerous environmental and economic problems. This study addresses these challenges by reviewing existing research to identify gaps in knowledge and aims to assess the profitability of green banking activities in Bangladesh. The research focuses on how green banking activities, guided by specific policy frameworks, can contribute to financial performance. However, it explores not only the profitability of these activities but also the associated challenges and opportunities, providing prospects, suggestions, and recommendations for selected banks. The statistical techniques are used, i.e., descriptive statistics, graphic presentations, ANOVA, post-hoc test (LSD), linear regression in SPSS, and regression for panel data in Gretl, etc. After analyzing the data, the results of this study inform us of the theoretical understanding by statistical proved for areas of policy guidelines of green banking practice and informs us empirical understanding by statistical verified for the profitability of green banking activities regarding policy guidelines of green banking by selected SCBs & PCBs. Finally, it is observed comparatively among SCBs, the RBL is the best performer, and among PCBs, the IBBL is the best performed comparatively, but JBL among SCBs and BAL among PCBs are in the most unfavorable position comparatively. The implications of the empirical analysis on the profitability of green banking activities among selected banks (SCBs and PCBs) in Bangladesh extend beyond the immediate financial realm, encompassing environmental sustainability, regulatory compliance, and the long-term viability of the banking sector.